Does GSS Still Maintain Relevance on HAART Outcome After the Introduction of Newest Active Antiretroviral Drugs? 48 Weeks Results - Ortu, Massimiliano; PaolaVitiello; Adorni, Fulvio; Rossotti, Roberto; Di Vincenzo, Paola; Vigano, Ottavia; Galli, Massimo; Rusconi, Stefano (Current HIV Research, 2011)
Background: Since recent observations demonstrated that extended resistance to protease inhibitors, nucleosidic and non - nucleosidic retrotranscriptase inhibitors (PI, NRTI, NNRTI) is a marker of disease progression and death, it is a matter of the greatest importance that experienced human immunodeficiency virus (HIV) - infected patients with limited therapeutic options receive a suppressive therapy pending the availability of at least two new antiretroviral drugs. Aim of the present study is to evaluate if the GSS score, calculated by analyzing the resistance to historical antiretroviral drugs and drug classes, is still relevant since several new potent drugs and drug classes entered the current clinical use. Methods: Taking into account patients without suppression of HIV replication for ≥ 6 months from October 2008 and October 2009, we analyzed viroimmunological and resistance data of 38 outpatients starting their last antiretroviral regimen including at least one of the following: maraviroc, enfuvirtide, raltegravir, etravirine, darunavir/ritonavir or tipranavir/ritonavir. Mutations present in all available genotypic resistance tests were recorded for each patient and then correlated to GSS value, assessed using the last genotypic ribonucleic acid (RNA) resistance test. GSS was studied as predictor of virological treatment outcome by univariate and multivariate logistic regression. Results: At 48 weeks, undetectable viral load was obtained in 80% of patients without difference between GSS classes (HIV-RNA median <50copies/ml); 95.8% of patients with baseline HIV-RNA <50,000copies/ml obtained virological suppression (p=0.003). 48 weeks CD4+ median value was 412 cells/μl considering GSS1 and 300 cells/μl for combined GSS2 and GSS3 scores. Data also showed a > 60% recurrence of specific mutations for NRTI: M41L, M184IV, L210W, T215FY, K219EQ and 75% for D67N. K103N and Y181CIV mutations for NNRTI persisted in 35% of cases and their prevalence incresed in parallel with the number of GRTs. About 60% of tests reported L10FIRVC, M36ILV, M46IL, I54VLAMTS, V82AFTSLI, and L90M mutations in the protease region. 63P mutation was found in a total number of GRTs close to 80%. This percentages, when correlated to GSS, revealed a distinct pattern for most mutations, that showed a greater prevalence for GSS = 2. Conversely, only NNRTI 181CIV and NRTI 210W showed larger numbers in GSS1 and GSS3. Conclusions: Single drugs belonging to new antiretroviral classes did not correlate to viroimmunological success for any GSS. High frequency and recurrence over GRTs for specific mutations confirm their key role following the exposure to ARVs classes. A baseline HIV-RNA <50,000 cp/ml is a predictor of therapeutic success and a carefully selected HAART based upon the evaluation of GRTs can favorably influence the immunovirologic response.
Keywords: tipranavir/ritonavir